Isoniazid acetylating phenotype in patients with paracoccidioidomycosis and its relationship with serum sulfadoxin levels, glucose-6-phosphate dehydrogenase and glutathione reductase activities - Barraviera, Benedito [UNESP]; Pereira, Paulo Câmara Marques [UNESP]; Machado, J. M. [UNESP]; De Souza, M. J. [UNESP]; Lima, C. R G [UNESP]; Curi, P. R. [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Meira, D. A. [UNESP] (FapUNIFESP (SciELO), 1991)
The authors evaluated the isoniazid acetylating phenotype and measured hematocrit, hemoglobin, glucose-6-phosphate dehydrogenase and glutathione reductase activities plus serum sulfadoxin levels in 39 patients with paracoccidioidomycosis (33 males and 6 females) aged 17 to 58 years. Twenty one (53.84%) of the patients presented a slow acetylating phenotype and 18 (46.16%) a fast acetylating phenotype. Glucose-6-phosphate-dehydrogenase (G6PD) activity was decreased in 5(23.80%) slow acetylators and in 4 (22.22%) fast acetylators. Glutathione reductase activity was decreased in 14 (66.66%) slow acetylators and in 12(66.66%) fast acetylators. Serum levels of free and total sulfadoxin were higher in slow acetylator (p _ 0.02). Analysis of the results permitted us to conclude that serum sulfadoxin levels are related to the acetylator phenotype. Furthermore, sulfadoxin levels were always above 50 μg/ml, a value considered therapeutic. Glutathione reductase deficiency observed in 66% of patients may be related to the intestinal malabsorption of nutrients, among them riboflavin, a FAD precursor vitamin, in patients with paracoceidioidomycosis.
Keywords: glucose 6 phosphate dehydrogenase; glutathione reductase; hemoglobin; isoniazid; sulfadoxine; sulfonamide; trimethoprim; acetylation; adult; blood sampling; clinical article; controlled study; drug blood level; enzyme activity; female; hematocrit; human; male; oral drug administration; phenotype; south american blastomycosis; Acetylation; Adult; Female; Glucosephosphate Dehydrogenase; Glutathione Reductase; Human; Isoniazid; Male; Middle Age; Paracoccidioidomycosis; Phenotype; Sulfadoxine; Support, Non-U.S. Gov't